Downsizing [videorecording (DVD)] - Payne, Alexander, 1961-; Damon, Matt; Waltz, Christoph, 1956-; Chau, Hong, 1979-; Wiig, Kristen, 1973-; Sudeikis, Jason (Paramount Home Entertainment, 2018)
When scientists find a way to shrink humans to five inches tall, Paul and Audrey Safrane decide to ditch their stressed out lives in order to get small and live large in a luxurious downsized community. Filled with life-changing adventures and endless possibilities, Leisureland offers more than riches, as Paul discovers a whole new world and realizes that we are meant for something bigger.